2019
DOI: 10.1097/md.0000000000016497
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging to detect myelolipomas of the liver

Abstract: Rationale: Primary hepatic myelolipoma is a rare benign neoplasm comprising mature adipose tissue and marrow components in various proportions. Chemical shift imaging (CSI) can distinguish the lipid within the tumor clearly; however, there have been no reports on the CSI of hepatic myelolipoma. Patient concern: A 20-year-old woman visited our hospital after discovering a space-occupying lesion in the liver with a history of more than 1 year. She felt distension pain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In addition, Golgi protein (GP)-73 is also a common diagnostic marker for liver cancer, which presents an extremely low or no expression in hepatocytes and high expression in hepatocytes infected with hepatitis B virus or adenovirus. Previous studies have reported higher sensitivity but lower specificity of GP-73 than AFP assay in the early diagnosis of PLC [ 12 , 13 ]. Currently, there is no report on the application of MRI combined with AFP-L3 and GP-73 in the diagnosis of primary liver cancer in China.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Golgi protein (GP)-73 is also a common diagnostic marker for liver cancer, which presents an extremely low or no expression in hepatocytes and high expression in hepatocytes infected with hepatitis B virus or adenovirus. Previous studies have reported higher sensitivity but lower specificity of GP-73 than AFP assay in the early diagnosis of PLC [ 12 , 13 ]. Currently, there is no report on the application of MRI combined with AFP-L3 and GP-73 in the diagnosis of primary liver cancer in China.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of hepatic myelolipoma is unknown, but several hypotheses exist. Among the most promising ideas are that it is due to an ectopic adrenal gland, an alteration of hepatocytes, or embryonic stem cells remaining in the liver[ 1 , 4 ]. Extra-adrenal myelolipomas tend to occur after middle age, with a male-to-female ratio of 1:2[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the most promising ideas are that it is due to an ectopic adrenal gland, an alteration of hepatocytes, or embryonic stem cells remaining in the liver[ 1 , 4 ]. Extra-adrenal myelolipomas tend to occur after middle age, with a male-to-female ratio of 1:2[ 4 ]. Myelolipoma is usually asymptomatic in the case of a small lesion, but spontaneous rupture due to mass effect, acute abdomen, and bleeding may occur as the lesion grows[ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-enhanced CT attenuation of fatty lesions in the liver is lower than 40 HU or at least 10 HU lower than that of the spleen [ 4 5 ]. These lesions may show variations depending on the proportion of fat and other components [ 7 8 ]; therefore, histopathological analysis is needed to confirm fatty lesions.…”
Section: Discussionmentioning
confidence: 99%